Development of contextual-based digital mathematics learning media for junior high school students - Hakim, Luqman Nur; Hartanto, Suryo; Amelia, Fitrah; Sitanggang, Pardomuan (CAHAYA PENDIDIKAN, 2023)
Learning Media used in the learning process is not optimal, students have difficulty in understanding mathematical concepts.Digital Learning media are needed according to the needs of students, which are easily accessible and support students in internal and external learning activities. The purpose of the research is to develop contextual-based digital mathematics learning media for Junior High School students that are valid, practical, and effective. Types of research, Research Development with ADDIE Development model: Analysis, Design, Development, Implementation and Evaluation. The study was conducted with students subject SMPN 51 Batam. Research instruments in the form of questionnaires of material experts, media experts, student response questionnaires, educator response questionnaires and learning outcomes test questions, were declared valid and reliable. Based on the results of the study, the development of Learning media achieved aspects of the validity of the material expert at 3.78 (very valid) and media expert 3.77 (very valid), small group trials 82.62 percent (practical) and the response of educators 90.83 percent (very practical). and aspects of media effectiveness 73.68 percent (effective). Based on the results of the study, it was concluded that contextual-based digital mathematics learning Media for Junior High School students that have been developed are valid, practical and effective, developed media can be chosen as an alternative for learning mathematics causes attractive and interactive design view, with contextual mathematics.